2012
DOI: 10.1007/s10899-012-9346-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-Identification as a Moderator of the Relationship Between Gambling-Related Perceived Norms and Gambling Behavior

Abstract: This research was designed to evaluate social influences and perceived social norms on gambling behavior among undergraduate students. Furthermore, this research was designed to replicate and extend previous research demonstrating that young adults overestimate the prevalence of gambling among peers, and that the magnitude of overestimation is positively associated with own use (Larimer and Neighbors, Psychol Addict Behav 17:235–243, 2003). We expected that; (1) gambling college students would identify more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…The initial validation of the scale (Neighbors et al, 2002) revealed wins and losses to be highly correlated and that these items are significantly associated with several frequently used gambling outcomes measures, including SOGS, Gamblers Anonymous 20, and the Gambling Attitudes and Beliefs Scale. Previous results using this measure indicate that people are more likely to exaggerate wins than losses, suggesting a need to differentiate them (Foster et al, 2014). …”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The initial validation of the scale (Neighbors et al, 2002) revealed wins and losses to be highly correlated and that these items are significantly associated with several frequently used gambling outcomes measures, including SOGS, Gamblers Anonymous 20, and the Gambling Attitudes and Beliefs Scale. Previous results using this measure indicate that people are more likely to exaggerate wins than losses, suggesting a need to differentiate them (Foster et al, 2014). …”
Section: Methodsmentioning
confidence: 95%
“…Foster and colleagues (2014) examined whether identifying with other gambling college students moderated the association between perceived gambling norms and gambling behaviors. Results showed that identification with gambling students was more strongly associated with gambling behavior than identification with students in general.…”
Section: Social Identity Theorymentioning
confidence: 99%
“…While the effects of family-related gambling remain relatively stable over early development, peer gambling factors may be particularly important for initiation and maintenance of gambling in adolescence (Foster et al 2015; Foster et al 2014; Gupta and Derevensky 1997). Adolescents with at-risk/problem gambling are more likely to have friends who also gamble (Gori et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Gambling-related perceptions have been linked to engagement in gambling (Foster, Neighbors, Rodriguez, Lazorwitz, & Gonzales, 2014; Leeman et al, 2014) and substance-use behaviors (Leeman et al, 2014). Extant literature related to adolescent perceptions about gambling indicates that perceptions of family and friends’ support for refraining against gambling may protect against problem gambling (Hardoon, Gupta, & Derevensky, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, relative to non-problem gamblers, at-risk/problem gamblers are more likely to have friends who gamble, and are also more likely to approve of gambling behavior (Gori et al, 2014). Additionally, perceived norms for gambling (e.g., perceiving that gambling is prevalent among or more accepted by peers) have been tied to gambling behavior (Foster et al, 2014). …”
Section: Introductionmentioning
confidence: 99%